Implementation of Strict Liability by Companies in Cases of Environmental Damage in Indonesia: An Overview of State Administrative Law in Indonesia - Muhammad Ainurrasyid Al Fikri (Indonesian State Law Review, 2022)
Strict liability in the context of companies in environmental damage refers to the legal principle which states that companies can be held fully responsible for environmental damage resulting from their operational activities, without having to prove the fault or negligence of the company. This means that the company can be held responsible for environmental damage caused, whether intentionally or unintentionally. This study used normative legal research, while the approaches used are combining statutory, a conceptual and a case approach. The development of strict liability in positive law in Indonesia has experienced development and refinement over time, indicated by the application made in several cases concerning environmental violations by several irresponsible parties. Basically, the implementation of strict liability really helps the aggrieved parties, especially the common people, in enforcing environmental laws in Indonesia. The principle of strict liability in environmental damage has a number of important implications. First, companies are required to take careful precautions in their operations to prevent environmental damage. They must follow strict environmental standards and implement suitable technologies to reduce their negative impact on the environment. Second, companies must pay compensation for environmental damage resulting from their operations, even if they are not to blame for the damage. The principle of strict liability eliminates the need to prove the company's fault or negligence, therefore that the company must be financially responsible for the environmental losses incurred.